Carbofuran effects in soil nematode communities: using trait and taxonomic based approaches - Chelinho, Sónia (2019)
This work intends to implement the use of native soil nematode communities in ecotoxicological tests using a model pesticide and two geographically nematode communities (Mediterranean and sub-tropical) in order to obtain new perspectives on the evaluation of the toxic potential of chemical substances. The environmental condition of the nematode communities was described using a trait-based approach (grouping the organisms according to their feeding traits) and a traditional taxonomic method (identification to family level). Effects on total nematode abundance, number of families and abundance of nematode feeding groups as well as potential shifts in both trophic and family structure were assessed. Agricultural soils from Curitiba (Brazil) and Coimbra (Portugal) were sampled and the corresponding nematode communities were extracted. Part of the collected soil was defaunated and spiked with four doses of a carbofuran commercial formulation. Afterwards each of the replicates was inoculated with a nematode suspension containing ≈200 or 300 nematodes. After 14 and 28 d of exposure the nematodes were extracted, counted and identified at family level and separately classified according to their feeding traits. The patterns of nematode responses revealed a decrease in the total abundance and a reduction in the number of families. Despite the similar effects observed for both communities, statistically significant toxic effects were only found within the Portuguese community. The total nematode abundance was significantly reduced at the highest carbofuran concentrations and significant shifts in the family structure were detected. However, the trophic structure, i.e., the contribution of each feeding group for the overall community structure, did not significantly change along the contamination gradient. Results showed that using such a trait-based approach may increase the ecological relevance of toxicity data, by establishing communalities in the response to a chemical from two different taxonomic communities, although with potential loss of information on biodiversity of the communities.